(untitled) (Zaporizhzhia Historical Review, 2021)
The similarity of the modernizational processes of the transformation of the orthodox confessions of Ukraine of the 20-30-th years XX c with the modernizational processes in the churches of the other folks was analyzed. The ways and the level of the spreading of the national and cultural influences on the religious way of thinking of Ukrainians in the USSR was followed.